Monument of history – procedures of recognition and selection criteria on the example of the town of Trzebiatów, a candidate for the title - Latour, Agnieszka (Protection of Cultural Heritage, 2019)
The Mayor of Trzebiatów's application to recognize the Old Town Complex in Trzebiatów as a Monument to History was submitted to the Minister of Culture and National Heritage in April 2011. Trzebiatów is a town located in the poviat (district) of Gryfice, in the Zachodniopomorskie Voivodeship. The basis for submitting the application for the title of the Monument of History was the following: - Preserved medieval urban layout of the Old Town complex with a clear cadastral division; - Preserved historical buildings within the defensive walls, - Entry of the Old Town area into the register of historical monuments; - 40 objects within the Old Town boundaries are entered into the historical monuments register; - In the Old Town there is a local spatial development plan in the form of a revaluation plan, adopted by the Trzebiatów City Council in 1996. The outline of the city's history as well as conservation and planning activities are presented, indicating at the same time its material and non-material values. The conclusion expressed the conviction that these values meet the selection criteria set by the Ministry of Culture and National Heritage.